Concentrating solar power for less than USD 0.07 per kWh: finally the breakthrough? - Lilliestam, Johan; Pitz-Paal, Robert (Renewable Energy Focus, 2018)
The cheap power purchase agreements (PPAs) for two recent concentrating solar power (CSP) projects in Australia (Aurora) and Dubai (DEWA IV) raise questions of how such low costs can be achieved, and whether this could mark the commercial breakthrough of this technology. Here, we investigate these projects with the information available, and seek reasons for the low PPAs. Both projects have low technology costs – which are prerequisites but insufficient as explanations for the low bids. For Aurora, a key explanation is its business model that allows it to sell power outside the PPA, during high-price times when the sun sets and the growing PV fleet goes offline, revealing the market value of CSP. For DEWA IV, a key factor is its extraordinarily long PPA duration, but we expect that it also has very low financing costs. We conclude that both projects can probably be replicated, either in places with an increasing PV fleet and strong “duck curve” problems (replicating Aurora) or in places with low policy risks and access to cheap capital (replicating DEWA IV); such places could include the US, Southern Europe, or the Gulf region.
CRIS-Team Scopus Importer:2023-06-14